PENGARUH JUMLAH PASOKAN, JUMLAH TENAGA PRODUKSI DAN MASA PANEN PASOKAN TERHADAP VOLUME PRODUK OLAHAN UDANG PT MISAJA MITRA PATI - Hesti Anugraheni; Yusmar Ardhi Hidayat; Azizah Azizah (JOBS (Jurnal Of Business Studies), 2017)
Shrimp is superior commodity in Indonesia. Beside as material in production, shrimp are sold to another countries. This research aims to analyze the influence of raw material, worker in production, and harvest period of shrimp to the volume of shrimp processed product in PT Misaja Mitra Pati. Method of analysis data are literature review and interview. The technique of analysis used in this research is multiple linear regression analysis. Based on the research that had been done, there are three factors that significant with a significance level α = 0.05, either simultaneously or partially on the volume of shrimp processed product in PT Misaja Mitra Pati, namely raw material, worker in production, and harvest period of shrimp. The results of F-test, shows that F sig. value about (0.000) < significance level (α = 0.05). It means that raw material, worker in production, and harvest period of shrimp are significant effect on the volume of shrimp processed product in PT Misaja Mitra Pati simultaneously. Based on the result of t-test, partial raw material had significant and positive effect on the raw material in PT Misaja Mitra Pati with sig. value about 0.026 < α = 0.05 sig. level and the coefficient of 0.099, worker in production is significant and positive effect on the volume of shrimp processed product in PT Misaja Mitra Pati with significant value about 0,000< α = 0.05 sig. level and the coefficient of 0.920, while harvest period of shrimp significant and positive affect on the volume of shrimp processed product in PT Misaja Mitra Pati with significant value about (0,028) < sig. level (α =0.05) and the coefficient 3.470. Based on the adjusted R2 value about 0,857, which means 85.7% change in the volume of shrimp processed product in PT Misaja Mitra Pati could be explained by three independent variables that were raw material, worker in production, and harvest period of shrimp, while the rest of 14,3% is explained by the other variables outside the model.